Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.berh.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic degenerative disorder characterized by cartilage loss. Its prevalence is high, and it is a major cause of disability. The cause of OA is not known; however, current evidence indicates that it is multifactorial. Major risk factors for osteoarthritis are age, female sex, obesity, geographic factors, occupational knee-bending, physical labour, genetic factors and race, joint trauma, vitamin D deficiency, and chondrocalcinosis. Osteoarthritis causes joint pain, stiffness, and limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 83 publications
2
78
0
3
Order By: Relevance
“…This is coincident with the previous conclusion that obesity and gender are major risk factors for knee OA. 17 Our results showed that age was an independent risk factor in the overweight group. In this group, the frequency distribution of two genotypes (AA at rs12706832 and TT at rs2071045) was different.…”
Section: Discussionmentioning
confidence: 48%
“…This is coincident with the previous conclusion that obesity and gender are major risk factors for knee OA. 17 Our results showed that age was an independent risk factor in the overweight group. In this group, the frequency distribution of two genotypes (AA at rs12706832 and TT at rs2071045) was different.…”
Section: Discussionmentioning
confidence: 48%
“…1) OA is characterized by progressive degradation of articular cartilage and chondrocytes apoptosis and death. 2) Chondrocytes apoptosis has been identiˆed as a vital reason for cell loss and is now considered as an important factor contributing to degradation of extracellular matrix (ECM) in OA cartilage. 3) Many researches have also demonstrated that enzymatic cleavage by matrix metalloproteinases (MMPs) together with cytokines plays critical roles in the initiation and progression of cartilage destruction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that OA is not the result of a single genetic anomaly but rather it is under the influence of multiple genes and environmental factors. Genetic analyses have shown that ADAM12, BMP2, CD36, COX2, NCOR2 genes are related to OA and associations of loci on the 2nd, 4th, 6th, 7th, 11th, 16th chromosomes and X chro- mosome with OA have been demonstrated (21). Relationships between different HLA alleles and OA or OA variants are also known.…”
Section: Discussionmentioning
confidence: 99%